Vibrio Species and Cyanobacteria : Understanding Their Association in Local Shrimp Farm Using Canonical Correspondence Analysis (CCA) - Dayang Najwa, Awg Baki; Elexson, Nillian; Dalene, Lesen; Teng, Sing Tung (Springer Nature, 2024)
In aquatic environments, Vibrio and cyanobacteria establish varying relationships infuenced by environmental factors. To investigate their association, this study spanned 5 months at a local shrimp farm, covering the shrimp larvae stocking cycle until harvesting. A total of 32 samples were collected from pond A (n = 6), pond B (n = 6), efuent (n = 10), and infuent (n = 10). Vibrio species and cyanobacteria density were observed, and canonical correspondence analysis (CCA) assessed their correlation. CCA revealed a minor correlation (p = 0.847, 0.255, 0.288, and 0.304) between Vibrio and cyanobacteria in pond A, pond B, efuent, and infuent water, respectively. Notably, Vibrio showed a stronger correlation with pH (6.14–7.64), while cyanobacteria correlated with pH, salinity (17.4–24 ppt), and temperature (30.8–31.5 °C), with salinity as the most infuential factor. This suggests that factors beyond cyanobacteria infuence Vibrio survival. Future research could explore species-specifc relationships, regional dynamics, and multidimensional landscapes to better understand Vibrio-cyanobacteria connections. Managing water parameters may prove more efcient in controlling vibriosis in shrimp farms than targeting cyanobacterial populations.